Revisiting the Kantian legacy in Habermas: the philosophical project of modernity and decolonial critiques to rationality and cosmopolitanism - Consani, Cristina Foroni (Studia Kantiana, 2023)
This paper deals with Amy Allen’s critique of Habermas's theory of modernity, democracy, and cosmopolitanism. I will focus on her arguments that touch on the role of rationality. Allen's critique of Habermas will be presented, especially where she argues that focusing on rationality is ethnocentric and promotes the political exclusion of subaltern groups. The extent to which Allen's critiques affect the emancipatory potential of Habermasian theory will next be assessed. It is finally argued that Allen's position leads to a denial of the distinction between social rationality and irrationality as legitimate criteria. The consequences of such a position for the political sphere will then be analyzed.